Depletion of New Neurons by Image Guided Irradiation - Tan, Yao-Fang; Rosenzweig, Shira; Jaffray, David; Wojtowicz, Jan M. (Frontiers in Neuroscience, 2011)
Ionizing radiation continues to be a relevant tool in both imaging and the treatment of cancer. Experimental uses of focal irradiation have recently been expanded to studies of new neurons in the adult brain. Such studies have shown cognitive deficits following radiation treatment and raised caution as to possible unintentional effects that may occur in humans. Conflicting outcomes of the effects of irradiation on adult neurogenesis suggest that the effects are either transient or permanent. In this study, we used an irradiation apparatus employed in the treatment of human tumors to assess radiation effects on rat neurogenesis. For subjects we used adult male rats (Sprague-Dawley) under anesthesia. The irradiation beam was directed at the hippocampus, a center for learning and memory and the site of neurogenic activity in adult brain. The irradiation was applied at a dose-rate 0.6 Gy/min for total single-fraction, doses ranging from 0.5-10.0 Gy. The animals were returned to home cages and recovered with no sign of any side effects. The neurogenesis was measured either 1 week or 6 weeks after the irradiation. At 1 week, the number of neuronal progenitors was reduced in a dose-dependent manner with the 50% reduction at 0.78 Gy. The dose-response curve was well fitted by a double exponential suggesting two processes. Examination of the tissue with quantitative immunohistochemistry revealed a dominant low-dose effect on neuronal progenitors resulting in 80% suppression of neurogenesis. This effect was partially reversible, possibly due to compensatory proliferation of the remaining precursors. At higher doses (> 5Gy) there was additional, nearly complete block of neurogenesis without compensatory proliferation. We conclude that notwithstanding the usefulness of irradiation for experimental purposes, the exposure of human subjects to doses often used in radiotherapy treatment could be damaging and cause cognitive impairments.